Profiles of women who help us to age in place. (2nd January 2020) - Butler, Sandra S.
ABSTRACT: As our population ages and people overwhelmingly prefer to age in place, the need for home care workers is steadily increasing. Unfortunately, due to the low value society places on caring work, filling these positions and retaining workers is a challenge. Drawing on a pilot study involving in-depth interviews with eight female home care aides, this brief report profiles three categories of worker perceptions of their jobs: "satisfied" (n = 3), "need more support" (n = 3), and "on my way out" (n = 2). Study participants liked their work but believed their jobs needed to be improved. Policy implications based on study findings are explored.